2012
DOI: 10.2174/1871523011202030267
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic and Anti-Angiogenic Effects of Benzimidazole Compounds: Relationship with Oxidative Stress Mediated Ischemia/Reperfusion Injury in Rat Hind Limb

Abstract: Ischemia/reperfusion (I/R)-induced injury is a pathophysiological process consisting of a complex cascade characterized by an increase in reactive oxygen species production, pro-inflammatory cytokine release, and activated endothelial cells leading to cell damage and death. The aim of this study was to investigate effects of substituted 2-benzylbenzimidazole derivatives, 2-(3-methoxybenzyl)benzimidazole (BB3) and 2-(4-methoxybenzyl)benzimidazole (BB4), on I/R-induced changes in the markers of oxidative stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The concept that hind limb I/R could exert oxidative stress in rats (Algul et al, 2012;Zhu et al, 2017) was confirmed by the present study, as our data revealed a statistically significant upregulation of iNOS immunoexpression in the lung tissue cells of rats undergoing hind limb I-R as compared to control. During I-R injury, it has been shown that oxidants (especially iNOS), infiltrated leukocytes, and inflammatory molecules can work together to injure the pulmonary microvasculature leading to a loss of microvascular integrity and eventually gas exchange impairment and pulmonary dysfunction (Wang le et al, 2002).…”
Section: Discussionsupporting
confidence: 84%
“…The concept that hind limb I/R could exert oxidative stress in rats (Algul et al, 2012;Zhu et al, 2017) was confirmed by the present study, as our data revealed a statistically significant upregulation of iNOS immunoexpression in the lung tissue cells of rats undergoing hind limb I-R as compared to control. During I-R injury, it has been shown that oxidants (especially iNOS), infiltrated leukocytes, and inflammatory molecules can work together to injure the pulmonary microvasculature leading to a loss of microvascular integrity and eventually gas exchange impairment and pulmonary dysfunction (Wang le et al, 2002).…”
Section: Discussionsupporting
confidence: 84%
“…The FDA has recently approved ROS generating monoclonal antibody based drugs for brain tumors. A similar kind of pro-oxidative, apoptotic and anti-angiogenic mechanism is also observed in RA derivatives (Oztekin et al, 2012).…”
Section: Biological Efficacy 391 Selective Efficacy Of the Salt Andsupporting
confidence: 62%
“…More recently, the treatment potency of benzimidazoles in diseases such as ischemia-reperfusion injury or hypertension, have also been reported [5].…”
Section: Introductionmentioning
confidence: 99%